2022
DOI: 10.3934/mbe.2022369
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on monitoring mental health using smart wearable devices

Abstract: <abstract> <p>With the continuous development of the times, social competition is becoming increasingly fierce, people are facing enormous pressure and mental health problems have become common. Long-term and persistent mental health problems can lead to severe mental disorders and even death in individuals. The real-time and accurate prediction of individual mental health has become an effective method to prevent the occurrence of mental health disorders. In recent years, smart wearable devices h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Separately, the emotional experience of connecting visually to a building façade or physical place can be measured using portable, wearable indicators of body indices. Those sensors give readings for activation, mood, and stress levels [69][70][71][72][73][74]. This type of measurement, available only now through instrumental miniaturization and AI software for processing the signals, will go far in confirming the model of this paper.…”
Section: External Validation Of the Model Using Portable Sensorsmentioning
confidence: 80%
“…Separately, the emotional experience of connecting visually to a building façade or physical place can be measured using portable, wearable indicators of body indices. Those sensors give readings for activation, mood, and stress levels [69][70][71][72][73][74]. This type of measurement, available only now through instrumental miniaturization and AI software for processing the signals, will go far in confirming the model of this paper.…”
Section: External Validation Of the Model Using Portable Sensorsmentioning
confidence: 80%
“…Some researchers indicated the importance of utilizing AI for monitoring mental health using smart wearables. Long et al [11] advocate the need to utilize AI-based wearable devices to collect physiological signals for mental health detection. The authors indicated that HRV (Heart rate variability), EEG (Electroencephalography), ST (Skin temperature) and GSR (Galvanic skin response) signals are the most effective parameter indicators for detecting the mental health condition.…”
Section: State-of-the-art Of Ai and Emotions Recognitionmentioning
confidence: 99%
“…19–25 They enable continuous monitoring of physiological signals, thus supporting clinical decisions and enhancing the management of mental health disorders. 26–29 For example, electroencephalogram (EEG) electrodes are developed for prolonged high-quality neurological state monitoring. 30,31 Unfortunately, their reliance solely on electrophysiological signals is inaccurate due to the diversity of symptoms in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] They enable continuous monitoring of physiological signals, thus supporting clinical decisions and enhancing the management of mental health disorders. [26][27][28][29] For example, electroencephalogram (EEG) elec- † Electronic supplementary information (ESI) available. See…”
mentioning
confidence: 99%